An Analysis of the Approach of Spatial Development Programs of the Tehran Metropolitan Region to Peri-Urban Areas: A Case Study of Pakdasht - Mohammad Sheikhi; Bita Khalili; Amin Masoudi (پژوهش‌های برنامه و توسعه)
Tehran's metropolitan region has always faced urban expansion into surrounding peri-urban areas. This issue presents a major challenge for urban policymakers. Pakdasht, like many pri-urban areas, has been significantly impacted by this phenomenon across regional, urban, and rural levels. While spatial planning documents have historically addressed peri-urban issues, their effectiveness in tackling these challenges remains a point of discussion.This study utilizes qualitative content analysis to assess the approach of Pakdasht's spatial planning system towards peri-urban development. MaxQda software facilitated the analysis of relevant spatial planning documents. The analysis identified nine key substantive and procedural issues regarding peri-urban development in Pakdasht.Substantively, physical infrastructure, institutional-legal frameworks, and economic considerations were the most prominent concerns. Procedurally, integrated and participatory planning received the most emphasis in the spatial development plans.However, the analysis reveals that despite acknowledging peri-urban challenges, these plans lack a comprehensive and coordinated mechanism to control, monitor, and organize development in these areas.